Effect of Rikkunshito on the expression of substance P and CGRP in dorsal root ganglion neurons and voluntary movement in rats with experimental reflux esophagitis. Issue 7 (9th April 2014) - Kondo, T.; Oshima, T.; Koseki, J.; Hattori, T.; Kase, Y.; Tomita, T.; Fukui, H.; Watari, J.; Miwa, H.
Abstract Background While there are reports that the herbal medicine rikkunshito (RKT) relieves upper gastrointestinal disease symptoms, the effect of RKT on primary afferent neurons is unknown. Methods A model of reflux esophagitis (RE) was implemented using male Wistar rats aged 6–7 weeks. Ten days after surgery, the total area of esophageal mucosal erosion sites was determined. Th8‐10 dorsal root ganglia (DRG) were dissected out and the expression of substance P (SP), calcitonin gene‐related peptide (CGRP), and phosphorylated extracellular signal‐regulated kinase 1/2 (p‐ERK1/2) was determined in DRG using immunohistochemistry. RKT (0.6%/WV) or omeprazole (OME) (10 mg/kg) was administered for 10 days beginning on the day after surgery. Voluntary movement was measured with an infrared sensor for 22 h each day. Key Results RE rats showed esophageal mucosal erosion and significantly increased number of SP/CGRP‐ and p‐ERK1/2‐immunoreactive neurons in DRG. Treatment with OME improved the size of erosive lesions in the esophageal mucosa of RE rats, while RKT did not. Treatment with RKT or OME significantly reduced the expression of SP/CGRP and p‐ERK1/2 in DRG, and significantly increased voluntary movement in RE rats. Conclusions & Inferences RKT inhibited the activation of ERK1/2 and decreased the expression of SP and CGRP in DRG of RE rats, which may be associated with the observed amelioration of voluntary movement.